A bibliometric analysis of research on Indigenous health in Australia, 1972-2008 - Gemma E. Derrick; Andrew Hayen; Simon Chapman; Abby S. Haynes; Berenika M. Webster; Ian Anderson (Elsevier, 2012)
Abstract Objective: To determine the growth patterns and citation volume of research publications referring to Indigenous health in Australia from 1972 to 2008 compared to seven selected health fields. Methods: Web of Science was used to identify all publications (n=820) referring to the health of Indigenous Australians authored by Australian researchers, 1972 to 2008. Citations for each publication were also captured. Growth was compared with selected health fields as well as with overall Australian research publications. Results: Research publications referring to Indigenous health, while remaining relatively small in number, grew at an average annual rate of 14.1%, compared with 8.2% across all fields of Australian research. The growth rate shown was equal second highest in our seven categories of health and medical research. However, Indigenous publications were cited significantly less than the Australian average. Conclusions: While there has been positive growth in publications referring to Indigenous health, the attention paid to this research through citations remains disappointingly low. Implications: Given that research concentration and impact can be an index of how seriously a nation considers a health problem, the low visibility of Australian research examining Indigenous health does not demonstrate a level of concern commensurate with the gravity of Indigenous health problems. Further investigation for the reasons for lower citations may identify potential intervention strategies.